2014
DOI: 10.1371/journal.pone.0101132
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits the Migration of Human Lung Adenocarcinoma A549 Cell Lines Involving JNK/MAPK Pathway

Abstract: ObjectiveMelatonin, an indolamine produced and secreted predominately by the pineal gland, exhibits a variety of physiological functions, possesses antioxidant and antitumor properties. But, the mechanisms for the anti-cancer effects are unknown. The present study explored the effects of melatonin on the migration of human lung adenocarcinoma A549 cells and its mechanism.MethodsMTT assay was employed to measure the viability of A549 cells treated with different concentrations of melatonin. The effect of melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 56 publications
1
66
0
3
Order By: Relevance
“…In the present study, the p38 and JNK pathways appeared to be activated at therapeutic concentrations of melatonin in a gastric adenocarcinoma cell line. However, it has been shown that melatonin significantly inhibits the migration of A549 cells, which may be associated with the downregulation of the JNK/MAPK signaling pathway (46). The results of the current study indicate that the activation of p38 and JNK by melatonin initiates a molecular proliferative response in SGC7901 cells.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In the present study, the p38 and JNK pathways appeared to be activated at therapeutic concentrations of melatonin in a gastric adenocarcinoma cell line. However, it has been shown that melatonin significantly inhibits the migration of A549 cells, which may be associated with the downregulation of the JNK/MAPK signaling pathway (46). The results of the current study indicate that the activation of p38 and JNK by melatonin initiates a molecular proliferative response in SGC7901 cells.…”
Section: Discussionmentioning
confidence: 48%
“…A decrease in the level of the p-p65/p65 protein in SGC7901 cells treated with 2 mM melatonin was observed at 12 h (P<0.05), with a maximal significantly decreased level at 24 h of ~0. 46 fold compared with that of the control cells (P<0.01; Fig. 4B).…”
Section: Resultsmentioning
confidence: 85%
“…The ability of tumor cells to migrate is an important prerequisite for tumor dissemination and metastasis (15,39). A number of studies have additionally indicated that melatonin may have antimetastatic properties and may be able to reduce migration and invasiveness in certain types of cancer, including glioblastoma (22,25), lung (26) and breast cancer cells (27)(28)(29). According to Ortíz-López et al (28) melatonin inhibits the migration process and cell invasion in breast cancer cells via the rho-associated-1 protein, by modulating the dynamic cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results have additionally indicated that melatonin may be capable of reducing migration and invasiveness in glioblastoma (22,25), lung (26) and breast cancer cells (27)(28)(29). However, much remains to be elucidated regarding the antimetastatic properties of melatonin in HCC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Each group of MAPKs is activated by a distinct kinase cascade in which a MAP3K or MEKK phosphorylates and activates a downstream dual-specificity MAP2K or MEK, which in turn stimulates MAPK activity through dual phosphorylation of threonine and tyrosine residues within a conserved tripeptide motif (Thr-X-Tyr). Phosphorylation of these threonine and tyrosine residues on MAPKs results in a conformational change that increases substrate accessibility and enhances catalysis (Zhou et al 2014). Activation of ERK is through phosphorylation by MEK (MAPK/ERK kinase) 1/2 in response to various cytokines and growth factors and mediates mitogenic and antiapoptotic signals primarily, whereas members of the JNK and p38 family of MAPKs were identified originally as mediators of cellular stress and are activated by MKK4/MKK7 and MKK3/MKK6, respectively (Lei et al 2014;Moon and Park 2014;Yao et al 2014;Zhou et al 2014).…”
Section: Introductionmentioning
confidence: 99%